Framing Analysis of Putin Political Communication in Tempo Magazine - Abdul Rani Usman; Azman Sulaiman; Hamdani M.Syam; Deni Yanuar (Ikatan Sarjana Komunikasi Indonesia, 2023)
This article discusses the political communication of Russian President, Vladimir Putin who is influential in the European region to dominate world politics along with the United States. This competition repeats the history of the Soviet Union when President Mikhail Gorbachev took office. During Gorbachev's reign, Ukraine was part of the Soviet Union. Political competition between the West, the United States and the Soviet Union, makes Putin a communicator of world politics rivaling European and American leaders. Following the split of the Soviet Union, there was a cold war between the United States and Russia, leading to the emergence of a single American superpower. By the end of 2021, Russia will have military units stationed close to the border with Ukraine. The reason behind the incident was Ukraine's desire to join NATO. Putin sent forces to assault Ukraine on February 24, 2022, as a result of this political phenomenon. Conspiracy theory is employed in this study. Agenda Setting uses a sustaining theory and Theory News construction from Bennett is considered suitable According to research, Tempo's international political news demonstrates Russia's commitment to regaining its former prominence through a variety of characteristics, including its economic and military prowess. Russia is concerned about NATO-US threats, and vice versa Thousands of civilians were murdered and maimed as a result of US-NATO paranoia about Russia, leading to Russian military incursion into Ukraine. There was a global food crisis as a result of the Russian-Ukrainian conflict.